Gabon : Request for Stand-By Arrangement; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report, 2007)
This paper examines Gabon's request for a Stand-By Arrangement in support of its economic program. The arrangement provides access at 50 percent of quota. Given its strong balance of payments position, it intends to treat the arrangement as precautionary. Gabon is ineligible for support under the Policy Support Instrument, which is limited to Poverty Reduction and Growth Facility-eligible countries. The critical objectives of the government's program are to prepare the economy for the post-oil era and to make decisive progress in poverty reduction.